Implementasi Performance Management dan Performance Appraisal di Pondok Pesantren Nurul Islam Mojokerto: Studi Kualitatif pada Pengelolaan Kinerja Pendidik dan Tenaga Kependidikan - M Ikmaluddin Alfi Hidayat; M Ainur Rokhman Wahid (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
The purpose of this research is to examine in depth the practice of performance management and performance evaluation in improving the performance of educators and education personnel at the Nurul Islam Islamic Boarding School in Mojokerto. This research also tries to analyze how Islamic values and pesantren traditions can be combined with the implementation of MSDM to help improve the quality of education through regular management, training, and professional human resource development. With a qualitative descriptive method, data was obtained by means of observation, interviews, and documentation from functionaries, educators, staff, and foundation representatives. The results of this study show that the implementation of MSDM in the Nurul Islam Islamic Boarding School is carried out through six main aspects, namely planning, recruitment, selection or selection, training and development, performance evaluation, and integration. This study also concluded that educators and education personnel play an important role not only as teachers and managers of Islamic boarding schools, but also as moral Qudwah (guides) and Uswah (examples or examples) in forming religious and ethical values to students. The effective implementation of MSDM at the Nurul Islam Islamic Boarding School has a great impact on improving the quality of human resources, especially teachers or educators, improving the performance of institutions, and developing Islamic education in the context of modern education.